ANALISIS LIVE STREAMING, FLASH SALE DAN E-WOM DALAM MENDORONG PERILAKU IMPULSIVE BUYING PRODUK SKINCARE SKINTIFIC PADA PLATFORM TIKTOK SHOP - Ulsatunnisa Ulsatunnisa; Linda Ayu Oktoriza; Maria Safitri; Imam Nuryanto (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the influence of Live Streaming, Flash Sale, and E-WOM on impulsive buying behavior on Skintific skincare products on the TikTok Shop platform. This study uses a quantitative approach, with the population being students of the Management Study Program at Dian Nuswantoro University. The sample was selected using a non-probability sampling technique with a purposive sampling method, and this study involved 98 respondents. The study results show that the third variable, namely Live Streaming, Flash Sale, and E-WOM, significantly influence impulsive buying behavior simultaneously and partially. The conclusion of this study contributes to the digital marketing literature while providing practical recommendations for e-commerce business actors to optimize these marketing elements in increasing sales.